Shear Behavior of Concrete Beams Reinforced with GFRP Shear Reinforcement - Heecheul Kim; Min Sook Kim; Myung Joon Ko; Young Hak Lee (International Journal of Polymer Science)
This paper presents the shear capacities of concrete beams reinforced with glass fiber reinforced polymer (GFRP) plates as shear reinforcement. To examine the shear performance, we manufactured and tested a total of eight specimens. Test variables included the GFRP strip-width-to-spacing ratio and type of opening array. The specimen with a GFRP plate with a 3×2 opening array showed the highest shear strength. From the test results, the shear strength increased as the strip-width-to-strip-spacing ratio increased. Also, we used the experimental results to evaluate whether the shear strength equations of ACI 318-14 and ACI 440.1R can be applied to the design of GFRP shear reinforcement. In the results, the ACI 440 equation underestimated the experimental results more than that of ACI 318.